Guru Tegh Bahadur : background and the supreme sacrifice : a collection of research articles - Talib, Gurbachan Singh, 1911- (Gurū Tegh Bahādara tījī shahīdī shatābadī prakāshana laṛī, 1976)
On the life and work of Tegh Bahadur, 1621-1675, 9th guru of the Sikhs.